ALGOFLORA BIODIVERSITY OF THE SORBULAK SEDIMENTATION LAKE AND THE RELEASE OF TOXIN-PRODUCING CYANOBACTERIA (Eurasian Journal of Ecology, 2024)
Microbial biodiversity represents the largest untapped reservoir for the potential discovery of new promising species of microorganisms. The purpose of this article is to study the abundance of algoflora and the isolation of potential toxin producers from the Sorbulak reservoir. 153 species of microalgae have been identified in the Sorbulak reservoir. The greatest diversity is observed among green algae (44%), which is typical for polluted aquatic ecosystems. In terms of quantitative composition, diatoms occupy the second place (24%). Of the certain species in the ecosystem of the Sorbulac reservoir, 20% are cyanobacteria and 11% are eugenic algae. Among certain cyanobacteria, 15 are potentially toxigenic organisms. 4 pure cyanobacteria cultures have been isolated from the Sorbulak reservoir. Among the isolated strains of cyanobacteria, the Microcystis aeruginosa strain turned out to be the most toxic in relation to the A.salina test object. In the biomass extract of cyanobacterium Microcystis aeruginosa, 3 structural variants of toxins–microcystins with molecular weight were identified: microcystine-LA - 910.61 m/z, microcystine-RR - 1038.52 m/z, microcystine-YR - 1045.47 m/z.Key words: biodiversity, cyanobacteria, algae, algoflora, toxin-producing cyanobacteria.